Peningkatan Hasil Belajar Fisika Siswa Dengan Model Pembelajaran Kooperatif Tipe Jigsaw Di Kelas X TBSM SMK Negeri 1 Batang Angkola - Robinson Harahap; Eni Sumanti Nasution; Kasmawati (Universitas Gara Nusantara Padangsidimpuan, 2023)
This study aims to determine the improvement of student learning outcomes by using the jigsaw type cooperative learning model. The sample of this study were students of class X TBSM with a total sample of 36 people. This type of research is classroom action research. The analysis technique uses the average value. The conclusion of this study is that there is an increase in learning outcomes using the jigsaw type cooperative learning model, this can be seen from an increase in the pre-cycle in terms of the average value of student learning outcomes, which is 46.39, increasing in the first cycle to 63.89 and in the second cycle 80.33. And if viewed from the student's completeness obtained from the pre-cycle complete 6%, the first cycle 53% and the second cycle 92%.